Ethics and Responsible Research and Innovation in Practice (Springer Nature, 2023)
This Open Access book aims to present practical contributions to the ethics governance framework, the conceptualization and characteristics of ethics tools, as well as the experience gained from their application in different institutions. Its main objective is to provide a practical and useful guide that will help other institutions to start introducing Research Ethics effectively in their organizations. The European initiative ETHNA System has designed an ethics governance framework that can be implemented following specific guidelines and tools that can help different types of institutions to promote and generate responsible research and innovation. The papers included in this book were organized in topical sections as follows: foundations; experiences and lessons learned; ethics tools in practice; and looking into the future: main challenges.